(untitled) (Basel Institute on Governance Working Papers, 2024)
Politics matters for the success of anti-corruption and asset recovery efforts. This Working Paper: • discusses the political and governance factors that affect the performance of the justice system in relation to anti-corruption and asset recovery; • provides guidance on assessing these factors systematically, including through a novel Assessment and Monitoring Framework; • reveals how to use these assessments to develop adaptive strategies to strengthen the justice chain in line with changing contexts. It fills an important gap by enabling the systematic assessment and monitoring of contextual factors that impact the effectiveness of justice systems in relation to anti-corruption and asset recovery. About this research The International Centre for Asset Recovery (ICAR) at the Basel Institute on Governance works with partner countries and their enforcement and judicial authorities to strengthen asset recovery capacity, practice and policy. Building on ICAR’s track record, this paper harnesses learning and experiences on thinking and working politically to strengthen the rule of law and deter corruption. It contributes to the global conversation on strategic anti-corruption and asset recovery reforms. Feedback is welcome as ICAR continues to develop its approach and strategies: email the author or info@baselgovernance.org. Funding for this research was provided by the ICAR core donor group: the Government of Jersey, Principality of Liechtenstein, Norwegian Agency for Development Cooperation (Norad), Swiss Agency for Development and Cooperation (SDC), UK Foreign, Commonwealth & Development Office (FCDO) and UK Home Office.